First Investigation of Seasonal Changes in the Ecological and Anatomical Traits of Launaea sarmentosa (Willd.) Kuntze (Compositae) on the Andaman Coasts, Thailand - Meksuwan, Yurachat; Sutthinon, Pornsawan; Fontaneto, Diego; Meksuwan, Phuripong (Trends in Sciences, 2025)
Launaea sarmentosa (Willd.) Kuntze, a creeping herb native to the Andaman coasts of Southern Thailand, faces significant threats from habitat loss and environmental changes following the 2004 tsunami. This study investigated its ecological and anatomical characteristics across 4 coastal sites in Phuket and Phang-Nga Provinces. The parameters were categorized into 4 groups: plant traits (including photosynthetic pigment contents and anatomical features), upper soil layer features (e.g., sand, clay, chloride, magnesium, and pH), lower soil layer features (e.g., sand, silt, nitrogen, phosphorus, calcium, chloride, and magnesium), and climatic variables (air temperature and relative humidity). Sampling was conducted during the rainy season (November 2023) and the dry season (April 2024). Results revealed significant seasonal and site-specific differences in plant traits. Shoot density and below-ground fresh weight were highest during the rainy season and at sites with moderate sunlight. The chlorophyll a/b ratio varied significantly between seasons and sites, while the total chlorophyll/carotenoid ratio differed between sites only. Leaf anatomical features also showed seasonal variation, with upper and lower epidermis thickness, mesophyll thickness, and upper epidermal cell area being greater in the dry season, while the lower epidermal cell area remained unchanged. In the upper-layer soil, chloride content was influenced by season, while sand, clay, magnesium, and pH varied significantly between sites. In the lower-layer soil, sand, silt, chloride, and magnesium varied seasonally, while nitrogen, phosphorus, and calcium showed site-specific differences. Climatic factors also showed both seasonal and spatial variability, with cooler temperatures and higher humidity during the rainy season, particularly at moderately sunny sites. In summary, L. sarmentosa appears to favor conditions with partial sunlight, moist soils, and clay-rich substrates. These conditions were associated with greater shoot density and biomass. The findings highlight the role of seasonal and site-specific factors and offer useful guidance for conservation and coastal ecosystem management. HIGHLIGHTS Seasonal variation affects shoot density, the below/aboveground biomass ratio, the chlorophyll a/b ratio, as well as the thickness of the leaf epidermis and mesophyll in Launaea sarmentosa. Site-specific variation also influences the growth of sarmentosa, which favors moderately sunny environments. Soil properties at the study sites were investigated for the first time. In the upper layer, Cl serves as a seasonal predictor, while soil pH, organic matter, P, K, Ca, and Mg act as site predictors. In the lower layer, Cl and Mg vary temporally, while N, P, and Ca vary spatially. The present study emphasizes the need for habitat conservation to protect natural populations of sarmentosa. GRAPHICAL ABSTRACT